Rancang Bangun Sistem Layanan Pengaduan Pusat Komputer Berbasis Website - Pratama, Jerio Putra; Adytia, Pitrasacha; Harianto, Kusno (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to design and develop a web-based Puskom Complaint Service System that facilitates integrated and transparent complaint reporting, handling, and monitoring processes. The system development method used is the Software Development Life Cycle (SDLC) Waterfall model, which consists of the stages of requirements analysis, system design, implementation, testing, and maintenance. The system is developed using the PHP programming language with the Laravel framework, MySQL as the database, and Vue.js as the front-end technology to provide a modern user interface. The result of this study is a web-based system that has been successfully implemented with key features, including registration and login for students and staff, an online complaint submission form, online complaint status updates (open, progress, resolved, rejected), and a monitoring dashboard. Functional testing using the Black Box Testing method shows that 10 test scenarios were successfully executed with a 100% success rate, indicating that the system functions as designed. It is expected that this web-based Puskom complaint service system can provide a more structured, efficient, and transparent solution, thereby improving the quality of information technology services at STMIK Widya Cipta Dharma.